Sociálně demografická analýza Královehradeckého kraje(okresů Hradec Králové, Jičín, Trutnov, Náchod a Rychnov nad Kněžnou) - Veselá, Jana (Univerzita Pardubice, 2002)
Social domographic view of Hradec Králové region from the point of view of the teritorial statistical EU - NUTS units as the component part of NUTS 2 Northeast.
Keywords: NUTS 2; demografická statistika; Hradec Králové; porodnost; úmrtnost; sociální politika